PENGARUH KESEHATAN BANK DENGAN MENGGUNAKAN PROFIL RISIKO, TATA KELOLA PERUSAHAAN, RENTABILITAS, DAN PERMODALAN TERHADAP NILAI PERUSAHAAN (Studi pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2013-2016) - Agustina, Lathifah Maulida (Jurnal Ilmiah Mahasiswa FEB, 2018)
This research aims to determine the effect of bank soundness that is measured using Risk Profile, Good Corporate Governance, Capital, and Earning (RGEC method) on the value of banking companies listed in the Indonesia Stock Exchange in the period of 2013-2015. The ratios being used are Non-Performing Loan for Risk Profile, Proportion of Independent Commissioners for Good Corporate Governance, Return on Asset for Earnings, and Capital Adequacy Ratio for Capital. From the population of all banking companies listed in the Indonesia Stock Exchange, 10 banking companies were selected as the sample using purposive sampling method. The data of this study were analyzed using multiple linear regression analysis. The results show that Non-Performing Loan has a negative and significant effect on firm value, that the Proportion of Independent Commissioners and Return on Asset have a positive and significant effect on firm value, and that Capital Adequacy Ratio has a negative and insignificant effect on firm value.Keywords: NPL, Proportion of Independent Commissioners, ROA, CAR